Cleaning up your mental mess : 5 simple, scientifically proven steps to reduce anxiety, stress, and toxic thinking - Leaf, Caroline, 1963- (Baker Books, a division of Baker Publishing Group, 2021)
"Bestselling author and neuroscientist offers 5 proven steps to help you overcome the unhealthy thinking habits that contribute to anxiety, depression, and intrusive thoughts, and replace them with positive thinking that leads to health, happiness, and success"--